Audit Knowledge, Self-Efficacy, and Career Motivation on Career Interest as a Public Accountant with Job Market Perception as a Moderating Variable - Nur Khoirotun Nasihah; Isnaini Anniswati Rosyida; Masyhadi (LP2M IAIN Palopo, 2026)
Although public accountants play a strategic role in maintaining financial transparency in Indonesia, their number is limited to around 2000 active people in the middle of KAP increasing from 472 in 2023 to 500 in 2026. This study analyzes the influence of audit knowledge, self-efficacy, and career motivation on accounting students' interest in pursuing a career as a public accountant with job market perception as a moderator, using an associative quantitative approach and Partial Least Squares (PLS-SEM) survey method. The population of accounting students at private universities in Lamongan Regency taking auditing courses was purposively sampled as many as 108 students (minimum fifth semester) through a five-point Likert scale questionnaire analyzed with SmartPLS 4.0 including descriptive statistics, validity/reliability tests, and bootstrapping. The results show that career motivation has a significant effect on career interest (β=0.494, p=0.004, t=2.920), while audit knowledge (β=0.150, p=0.222), self-efficacy (β=0.159, p=0.329), job market perception (β=0.056, p=0.692), and the moderating effect is not significant, the model explains 76.4% of the variance (R²=0.764). Universities need to increase career motivation through special programs to encourage public accounting interest.